TERAPI LATIHAN DAN MOBILISASI PATELLA PADA PEMAIN SEPAKBOLA PASCA OPERASI RUPTUR ANTERIOR CRUCIATE LIGAMENT DAN MENISCUS REPAIR: STUDI KASUS - Gomos Pranata Aritonang; Lucky Anggiat (Fakultas Vokasi Universitas Kristen Indonesia, 2024)
Football is a sport that is full of physical contact with a high risk of injury. Injuries in football most often occur in the lower limbs, one of which is ligament tears. Meniscus traumatic injuries are commonly linked with ligament tears. Surgery is often the preferred treatment option when there is a significant ACL tear, or when non-surgical management of a partial tear is unsuccessful. Additionally, surgical intervention is typically necessary in cases of medial and lateral meniscus rupture. Problems found in post-operative ACL and meniscus conditions include limited range of motion of the joint (LGS) in flexion and extension, swelling in the knee area, oedema in the knee area, pain with flexion and extension movements, tenderness on the surface of the knee and weakness of the thigh muscles and calves The role of physiotherapy in sports injury conditions is to restore, develop and maintain the movement and function of the knee joint by using manual treatment, increased movement, modalities, functional training and communication to achieve a return to sports. The study implemented an exercise therapy and patella mobilization program based on clinical guidelines. The evaluation results indicated a reduction in pain, increased joint range of motion, muscle strength, and functional ability. The use of exercise therapy and patella mobilization after surgery for anterior cruciate ligament and meniscus repair yields positive outcomes